Systematic Review and Meta-Analysis of the Benefit and Safety of Preoperative Administration of Steroid in Patients Undergoing Liver Resection - Yang, Lingpeng; Zhang, Zifei; Kong, Junjie; Wang, Wentao (Frontiers in Pharmacology, 2019)
Objective: To evaluate the benefit and safety of preoperative administration of steroid in patients undergoing liver resection. Methods: Randomized controlled trials (RCTs) which comparing preoperative administration of steroid in patients undergoing liver resection with control group were identified through a systematic literature search in PubMed, Embase, and Cochrane Library Central databases. This meta-analysis was carried out to assess the liver function, inflammatory response and postoperative complications after liver surgery. Results: Six RCTs including 411 patients were reviewed. The pooled result showed that there was no significant difference in the incidence of overall complications between the steroid group and the control group (OR, 0.57; 95% CI, 0.27-1.17; P=0.13). With respect to specific complications, no significant difference was detected between the two groups in infection complications (OR, 0.95; 95% CI, 0.13-6.95; P=0.96), wound complications (OR, 0.65; 95% CI, 0.32-1.33; P=0.24), liver failure (OR, 0.41; 95% CI, 0.10-1.64; P=0.21), bile leakage (OR, 0.57; 95% CI, 0.17-1.89; P=0.36) and pleural effusion (OR, 1.24; 95% CI, 0.55-2.78; P=0.60). For liver function, the level of serum total bilirubin (TB) on postoperative day 1 (POD1) was significantly decreased associated with the intervention of steroid (MD, -0.54; 95% CI, -0.94 to -0.15; P=0.007). However, no significant difference was found in the level of alanine aminotransferase (ALT) (MD, -69.39; 95% CI, -226.52 to 87.75; P=0.39) and aspartate aminotransferase (AST) (MD, -93.44; 95% CI, -275.68 to 88.80; P=0.31) on POD1 between the two groups. Serum IL-6 level on POD 1 (MD, -57.98; 95% CI, -73.04 to -42.91; P＜0.00001) and CRP level on POD3 (MD, -4.83; 95% CI, -6.07 to -3.59; P＜0.00001) were significantly reduced in the steroid group comparing to the control group. Compared with the control group, the level of early postoperative IL-10 was significant higher in the steroid group (MD, 17.89; 95% CI, 3.89 to 31.89; P=0.01). Conclusion: Preoperative administration of steroid in liver resection can promote the recovery of liver function and inhibit the inflammatory response without increasing postoperative complications. Further studies should focus on determining which patients would benefit most from the steroid.